2021
DOI: 10.1126/science.abe7790
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral visual projections exist in non-teleost bony fish and predate the emergence of tetrapods

Abstract: In most vertebrates, camera-style eyes contain retinal ganglion cell neurons that project to visual centers on both sides of the brain. However, in fish, ganglion cells were thought to innervate only the contralateral side, suggesting that bilateral visual projections appeared in tetrapods. Here we show that bilateral visual projections exist in non-teleost fishes and that the appearance of ipsilateral projections does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…Despite these limitations, the results of previous studies are consistent with our hypothesis that post‐mitotic neuronal properties have diverged among vertebrates (Azim et al., 2014 ; Eklöf‐Ljunggren et al., 2012 ; Kiehn, 2016 ; Vigouroux et al., 2021 ; Zhu et al., 2018 ). For example, Zhu et al.…”
Section: Discussionsupporting
confidence: 88%
“…Despite these limitations, the results of previous studies are consistent with our hypothesis that post‐mitotic neuronal properties have diverged among vertebrates (Azim et al., 2014 ; Eklöf‐Ljunggren et al., 2012 ; Kiehn, 2016 ; Vigouroux et al., 2021 ; Zhu et al., 2018 ). For example, Zhu et al.…”
Section: Discussionsupporting
confidence: 88%
“…5F), the development of the peripheral nervous system in a host of different phyla (Pende et al, 2018(Pende et al, , 2020) (Fig. 5G,H), as well as the emergence of binocular vision in vertebrates (Vigouroux et al, 2021) (Fig. 5I).…”
Section: Evolutionary Developmental Biology (Evo-devo)mentioning
confidence: 99%
“…Images (G,H) kindly provided by Marco Pende (Vienna University of Technology, Austria). (I) 3D light-sheet image of the brain of a spotted gar injected in the eyes with two cholera toxin β tracers (Vigouroux et al, 2021). Scale bars: 400 µm.…”
Section: Evolutionary Developmental Biology (Evo-devo)mentioning
confidence: 99%
“…In humans, Zic2 and EphB1 are both expressed in the temporal half of the retina also coinciding with the location of iRGCs and, in Xenopus , Zic2 is expressed in the retina during metamorphosis when a late-born ipsilateral projection is generated. However, in zebrafish and chicken Zic2 is not expressed in RGCs during development and accordingly these species lack an ipsilateral projection ( Herrera et al, 2003 ; Lambot et al, 2005 ; Murcia-Belmonte et al, 2019 ; Vigouroux et al, 2021 ). Interestingly, ectopic expression of Zic2 in zebrafish RGCs leads to the appearance of an ectopic ipsilateral projection ( Vigouroux et al, 2021 ), revealing that Zic2 is able to activate a transcriptional module that controls midline avoidance even in species that naturally lack an ipsilateral projection.…”
Section: Introductionmentioning
confidence: 99%
“…However, in zebrafish and chicken Zic2 is not expressed in RGCs during development and accordingly these species lack an ipsilateral projection ( Herrera et al, 2003 ; Lambot et al, 2005 ; Murcia-Belmonte et al, 2019 ; Vigouroux et al, 2021 ). Interestingly, ectopic expression of Zic2 in zebrafish RGCs leads to the appearance of an ectopic ipsilateral projection ( Vigouroux et al, 2021 ), revealing that Zic2 is able to activate a transcriptional module that controls midline avoidance even in species that naturally lack an ipsilateral projection. Recent reports have shown that non-teleost bony fish also have an ipsilateral retinal projection ( Vigouroux et al, 2021 ) but the function of this projection is still unknown and future experiments are needed to uncover this question and also to dilucidate the regulatory mechanisms that control this ancient ipsilateral projection.…”
Section: Introductionmentioning
confidence: 99%